Low rate of severe acute respiratory syndrome coronavirus 2 spread among health-care personnel using ordinary personal protection equipment in a medium-incidence setting. (September 2020) - Durante-Mangoni, E.; Andini, R.; Bertolino, L.; Mele, F.; Bernardo, M.; Grimaldi, M.; Cuomo, N.; Tiberio, C.; Falco, E.; Di Spirito, A.; Raffone, M.; Russo, M.G.; et al.
Graphical abstract: Image 1